The Naratology of Possible Worlds – Terms, Approaches, Horizons - JOVIĆ, Andrea (Anafora, 2023)
Due to its questioning of the status and origin of fictional texts, the narratology of possible worlds found its logical development in postclassical narratology. Looking for a fresh view on the concept of truth in fiction, the discipline introduced new terms such as world, a semantic domain projected by the text, and modality, a mode in which persons and objects exist in those worlds, which helped illuminate the nature of fiction and its pluriperspectivity in a far superior way than its predecessors. Namely, those range from the analytic logic, through Saussurean structuralism, to the theory of mimesis. Consequently, the narratology of possible worlds has opened new perspectives in classical narratological studies by introducing concepts such as tellability, designed to evaluate the aesthetic potential of a certain plot, or authentication, which explains the mechanisms through which the narrator acquires narrative authority. Research has been sparked in the field of theory of genre as well, where on the basis of existence or absence of certain attributes of the possible world it has become possible to determine the genre of a text. Due to its deep connections with the postclassical turn towards context and interdisciplinarity, the narratology of possible worlds still opens new horizons, especially in the field of media studies where, by integrating the concepts of immersion and interactivity, it strives to model an aesthetics which would holistically stimulate the recipient’s imagination.